Command shaping techniques for vibration control of a flexible robot manipulator - Mohamed, Zaharudin (Elsevier, 2004)
This paper presents an investigation into development of feed-forward control strategies for vibration control of a flexible robot manipulator using command shaping techniques based on input shaping, low-pass and band-stop filtering. A constrained planar single-link flexible manipulator is considered and the dynamic model of the system is derived using the finite element method. An unshaped bang–bang torque input is used to determine the characteristic parameters of the system for design and evaluation of the control techniques. Feed-forward controllers are designed based on the natural frequencies and damping ratios of the system. Simulation results of the response of the manipulator to the shaped and filtered inputs are presented in time and frequency domains. Performances of the techniques are assessed in terms of level of vibration reduction at resonance modes, speed of response, robustness and computational complexity. The effects of number of impulse sequence and filter order on the performance of the system are investigated. Finally, a comparative assessment of the input shaping and input-filtering techniques is presented and discussed.